Flight muscle and flight activity of Junonia almana (Lepidoptera: Nymphalidae) and Apis dorsata (Hymenoptera: Apidae) (Bangladesh Journal of Zoology, 2021)
Abstract not availableBangladesh J. Zool. 48(2): 465-472, 2020